An Assessment of the Efficacy of Local Authorities’ Developmental Bye-Laws as Instrument to mitigate Building Collapse in Southwest, Nigeria - Fayomi, Fidelis Olukayode; Otufowora, Oluwole Adelaja; Ngwoke, Nwora Valentine; Adie, Joy Oluwaseun (NIU Journal of Social Sciences, 2024)
One persistent problem in the nation is the terrible tendency of building collapses. This has hampered the advancement of infrastructure and resulted to fatalities, property destruction, and financial losses for Nigeria. The purpose of this study was to assess how local governments' building codes and development bylaws affected the number of building collapses in Nigeria. The pertinent literature on the subject was examined. To improve the research's findings, the Ogun State Urban Regional Planning Law of 2008 and the 2010 Lagos State Urban and Regional Planning and Development Law, which is used in conjunction with the National URP law, were also examined. As a research tool, structured questionnaires were used; 48 were distributed, and 41 (85.4%) were returned. The gathered data were shown and explained. According to the research project, building collapses in Nigeria might be decreased if policymakers and the government focused more on the problem of upholding developmental bylaws, made sure that these laws are updated to reflect the global trend of urbanization, and so forth. According to the survey, project managers should get familiar with the prerequisites for obtaining permissions and approvals. Developers should be made aware of the significance of local development bylaws, building regulations, and the code by the local authorities. Local authorities should also set up guidelines to incentivize new developers to follow building regulations and bylaws, as well as to construct safety precautions to lessen the likelihood of collapses in Nigeria. Keywords: Building collapse, Developmental bye-laws, Local authorities, Setback, URP law.